Evaluation of River Water Quality Based on Biotic Index of Benthic Macroinvertebrate as Bioindicator (Case study in Genjong River Wlingi Blitar East Java, Indonesia) - Izzati, Fadhila Nuril; Retnaningdyah, Catur (Universitas Brawijaya, 2022)
This research aims to determine the water quality profile of Genjong River based on physicochemical parameters of water and benthic macroinvertebrates as bioindicators. Sampling was carried out at four different location based on difference of human activity in surrounding. The sampling was done in triple repetition for each station. The activity of station 1 is ecotourism (as reference site or positive control in this study), Station 2 (livestock I), Station 3 (livestock II), and Station 4 (plantation). The water physicochemical parameters were measured including water and air temperature, water current velocity and discharge, conductivity, pH, DO, BOD, TSS, nitrate, and orthophosphate. The result from the identification and calculation of the benthic macroinvertebrates density was used to determine some diversity indices and biotic indices. The difference in the value of each water quality parameter was tested by One-way ANOVA. Based on the abiotic water quality profile, Genjong River water is included as the Class IV category based on Indonesia Government Regulation No. 22 of 2021 with a BOD value of 3.61 – 7.22 mg.L-1. Human activities along the Genjong River have a great impact on decreasing water quality as indicated by increasing of nitrate levels from 0.52 ± 0.07 mg.L-1 at Station 1 up to 0.85 ± 0.07 mg.L-1 at Station 4. Also, orthophosphate levels from 0.02 ± 0.01 mg.L-1 at Station 1 to 0.18 ± 0.02 mg.L-1 at Station 4. Meanwhile, based on benthic macroinvertebrates as bioindicators, Genjong River was classified as lightly (S1, H = 1.74) to moderately polluted (S4, H = 1.24) with toxic materials and slightly contaminated with organic matter (S4 with FBI value = 5.38). The decline in water quality was also shown by the decreasing ASPT value from 4.20 at Station 1 to 3.68 at Station 4.